2018
DOI: 10.3847/1538-4357/aaddfc
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Surface Magneto-convection as a Source of Astrophysical Noise. II. Center-to-limb Parameterization of Absorption Line Profiles and Comparison to Observations

Abstract: Manifestations of stellar activity (such as star-spots, plage/faculae, and convective flows) are well known to induce spectroscopic signals often referred to as astrophysical noise by exoplanet hunters. For example, setting an ultimate goal of detecting true Earth-analogs demands reaching radial velocity (RV) precisions of ∼9 cm s −1 . While this is becoming technically feasible with the latest generation of highly stabilised spectrographs, it is astrophysical noise that sets the true fundamental barrier on at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 30 publications
2
41
0
Order By: Relevance
“…In Fig. 21, we compare the observed line shifts with theoretical syntheses for Fe i 6301.5 Å (de la Cruz Rodríguez et al 2011) and Fe i 6302.5 Å (Cegla et al 2018). The synthesized line shifts agree with the observations within a margin of around ±100 m s −1 .…”
Section: Lines Around 6302 åsupporting
confidence: 68%
See 4 more Smart Citations
“…In Fig. 21, we compare the observed line shifts with theoretical syntheses for Fe i 6301.5 Å (de la Cruz Rodríguez et al 2011) and Fe i 6302.5 Å (Cegla et al 2018). The synthesized line shifts agree with the observations within a margin of around ±100 m s −1 .…”
Section: Lines Around 6302 åsupporting
confidence: 68%
“…However, it fails to reproduce the slope of the center-to-limb variation. In case of Fe i 6302.5 Å, the synthesis of Cegla et al (2018) manages to largely reproduce the slope of the observed center-to-limb variation. In anticipation of Sect.…”
Section: Lines Around 6302 åmentioning
confidence: 87%
See 3 more Smart Citations